Prediction of Cavitation Evolution and Cavitation Erosion on Centrifugal Pump Blades by the DCM-RNG Method - Han Zhu (Hindawi-Wiley, 2021)
Cavitation can reduce the efficiency and service life of the centrifugal pumps, and a long-term operation under cavitation conditions will cause cavitation damage on the surface of material. The external characteristic test of the IS65-50-174 single-stage centrifugal pump was carried out. Moreover, the cavitation mechanism under specific conditions was analyzed by numerical simulation. Considering the macroscopic cavitation flow structure in the centrifugal pump, three different cavitation erosion prediction methods were used to predict the erodible areas. The results show that the calculation results obtained by the density correction method (DCM) can well match the flow characteristics of the centrifugal pump under the rated conditions. When the centrifugal pump head drops by 3%, cavitation mainly occurs on the suction surface, and the cavity on the pressure surface is mainly concentrated near the front cover. The cavitation prediction method based on the time derivation of pressure change is not suitable for centrifugal pumps, while the prediction result of the erosive power method is more reasonable than the others. At time 0.493114 s, the maximum erosive power appears on the blade near the volute tongue, and its value is 1.46e−04 W.